Diversified Fund Management Strategy at Salaf Islamic Boarding Schools - Mursidah, Liqo’; Nadhir, Mirbahun (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Funding sustainability remains a critical challenge for Islamic boarding schools due to reliance on limited and fluctuating income sources. Specific Background At Salafiyyah Asy-Syafiiyyah Islamic Boarding School, dependence on contributions from students’ guardians has historically led to operational instability. Knowledge Gap Previous studies have not comprehensively mapped integrated funding diversification combining business units, productive waqf, stakeholder collaboration, and digital donation systems within pesantren contexts. Aims This study aims to analyze the implementation of a diversified funding strategy to support financial independence and institutional sustainability. Results Using a qualitative case study approach, findings reveal that diversification through business units, productive waqf, alumni networks, and digital infaq platforms generates stable income streams, increases stakeholder participation, and distributes financial resources more evenly throughout the year, with business units contributing approximately 20–25% of regular income and waqf assets providing long-term financial support. Novelty The study introduces an empirical model integrating traditional Islamic philanthropy with modern financial management practices and identifies stakeholder collaboration as a core element of a solidarity-based funding ecosystem. Implications These findings provide practical guidance for Islamic educational institutions to develop adaptive, professional, and sustainable financial management systems that strengthen resilience against economic fluctuations. Highlights: Multiple revenue streams distribute institutional income more consistently across operational periods. Waqf asset utilization generates continuous returns supporting long-term financing needs. Collective participation from internal and external actors forms a resilient funding ecosystem. Keywords: Islamic Boarding Schools, Funding Diversification, Financial Management, Productive Endowments, Institutional Independence.